Food Hoarding Behaviour of Pika (Ochotona) in Langtang National Park, Nepal - Koju, Narayan P; Chalise, Mukesh K (Journal of Natural History Museum, 2015)
The study was conducted on food hoarding behaviour of pika in Langtang National Park (LNP). It was carried along transect of 53 Km length and 200m wide from 3000 masl to 5200 masl in two routes (Langtang route and Gosainkunda route) from 2011 to 2013. Behaviours of pika were recorded from 5:30 to 19:30 during summer and from 6:30 to 17:30 during winter using focal scan sample method. Total 684 hours behaviours were recorded in 129 days covering all the seasons. Seven dry hay-piles were observed and 12 incidents of transferring food were observed. Pikas in Langtang were very poor in food hoarding and this behaviour was observed only in subalpine area.J. Nat. Hist. Mus. Vol. 28, 2014: 34-41